Reduction of Fetal Dose in Computed Tomography Using Anterior Shields. Issue 2 (March 2015) - Moore, William; Bonvento, Michael J.; Lee, Dwight; Dunkin, Jared; Bhattacharji, Priya
<x xml:space="preserve">Abstract</x> Objective The objective of this study was to assess the potential of anterior in beam bismuth shields placed on the abdomen and the pelvis of a RANDO phantom to decrease radiation dose to a simulated fetus. Methods Thermal luminescent dosimeters irradiated in a RANDO phantom were used to measure radiation dose at 0 weeks and 18 weeks after conception. An 18-week gestation was simulated by adding the corresponding equivalent of super-stuff to account for additional subcutaneous tissue. To assess image quality, a 461A body phantom with low contrast resolution phantom insert was used. The minimum size of low contrast resolution target visualize was recorded with no shielding and 25-cm-wide shielding. Results With shields, there was a radiation dose reduction of 19% to 23% at 0-week gestation and 16% to 24% at 18-week gestation. No qualitative difference was found in low contrast detectability with the shields. Conclusions These shields reduce fetal radiation exposure early in pregnancy with acceptable image quality.